2019
DOI: 10.15270/55-4-764
|View full text |Cite
|
Sign up to set email alerts
|

We Can’t Be Here Forever”: University Students’ Reflections on Terminating Community-Engagement Relationships

Abstract: Studies on community engagement (CE) focus on its benefits but not enough on termination and difficulties experienced at the personal level with exiting projects. A study on CE with service-learning students and volunteers at a South African university identified issues and themes pertaining to termination as systematic process, emotional responses to termination, and the need to find closure. This paper argues that termination should be more integral to CE processes, and considering that CE experiences can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…By means of interviews, focus group discussions and blogs, it has been found that students' motives for participating in service learning include seeking learning opportunities and doing good by helping others. 4,12,27 In addition to sharing their experiences and personal feelings, 6,28,29 students have also reflected on the perceived positive impact they have made on the communities in which they worked. 12,27,30 From the author's experiences and observation in the context of international service learning, students reflect on their experiences not only when formal research is conducted but also through opportunities for reflection included in the design of many service learning programmes.…”
Section: Students' Voicesmentioning
confidence: 99%
“…By means of interviews, focus group discussions and blogs, it has been found that students' motives for participating in service learning include seeking learning opportunities and doing good by helping others. 4,12,27 In addition to sharing their experiences and personal feelings, 6,28,29 students have also reflected on the perceived positive impact they have made on the communities in which they worked. 12,27,30 From the author's experiences and observation in the context of international service learning, students reflect on their experiences not only when formal research is conducted but also through opportunities for reflection included in the design of many service learning programmes.…”
Section: Students' Voicesmentioning
confidence: 99%
“…Conducting this project, we also anticipate another benefit of engaging local students in CenR, which is solving the issue of project termination. The impacts of students' involvement can have lasting effects (Fluks & Naidoo, 2019) as they develop an understanding of local issues and cultivate a sense of place attachment and personal awareness of sustainability for their future research or professional endeavors.…”
Section: Introductionmentioning
confidence: 99%